The impact of storage conditions on platelets in platelet-rich plasma (PRP) and platelet concentrate (PC) - Sriwastwa, Lucky; Shrivastava, Khushboo; Ashish Ranjan; C.P. Jaiswal; Sripati, Tirumala Kanakadurga (Student’s Journal of Health Research Africa, 2023)
Introduction: The ultimate aim of blood transfusion services is to give recipients whole blood and blood components that are secure, efficient, and potent. Control, assurance, and audit of quality are the foundational elements of quality. Product standards are developed and accurately met through the process of quality control. Method: In this study, samples of 2.3% PRBCs (50/2155), 9.3% platelet concentrate (42/451), and 3.6% of total whole blood collection (48/1,321) were prepared and tested for haematological parameters of quality control for the period from 1 January 2022 to 31 December 2022. Parameters for 8 samples of platelet concentrate available on day 5, were compared for day 0 and day 5. Result: Haematological metrics for whole blood, PRBCs, and platelet concentrate underwent quality examination. 50/2121, or 2.3% of the total whole blood collection, was used as a sample for the analysis of haematological parameters. Volume and hematocrit tests were performed on a total of 55 out of 2335 (2.3%) units. With a range of 344–365 mL, the average capacity was 358 mL. With a range of 35.1-48.0%, the mean hematocrit was 42.2%. Between 271 to 389 mL, the mean capacity was 311 mL. The range of the mean hematocrit was 57.3 to 81.9%. There was slight decrease in volume, platelet count and WBC count of platelet concentrates on day 5 as compared to day 0. Conclusion: For effective and safe blood transfusion services, continuous quality improvement is crucial. As a result, attention should be taken to apply consistent criteria for quality assessment, and objective analysis should be used on a regular basis to verify that consistent values are being followed.